The Effectiveness of the Old Criminal Code in Countering Online Gambling: An Analysis of Normative Weaknesses and a Comparison of Its Regulation with the ITE Law - Raehan Akbar Fadillah; Yuliana Yuli (UNIVERSITAS PAKUAN, 2026)
The rapid development of information technology has transformed conventional gambling into online gambling that operates through electronic systems and transcends territorial boundaries, posing a serious challenge to the implementation of the old Criminal Code designed to tackle conventional crimes. Although the study of online gambling and cybercrime has developed quite a bit, there has been no research that systematically compares the old Criminal Code and the ITE Law from various normative aspects while integrating the theory of legal effectiveness as an analytical framework. This study fills this gap by analyzing the effectiveness of the old Criminal Code, identifying its normative weaknesses, and comparing its regulation with the ITE Law using legislative, conceptual, and comparative approaches. The results of the study show that the old Criminal Code has fundamental limitations due to the formulation of criminal elements oriented to physical acts, territorial assumptions, and the absence of regulation of electronic evidence, while the ITE Law has proven to be more responsive and has a position as a lex specialis. The contribution of this research is the availability of multi-aspect comparative analysis that integrates Soerjono Soekanto's theory of legal effectiveness as an academic reference and practical basis for cyber criminal law policy reform in Indonesia. Keywords: Old Criminal Code; Online Gambling; THE WILL; Legal Effectiveness; Lex Specialis.